Rational design of a SHP-2 targeted, fluorogenic peptide substrate. Issue 17 (1st September 2019) - Ma, Elena S.; Barrios, Amy M.
Graphical abstract: Abstract: Protein tyrosine phosphatase (PTP) targeted, peptide based chemical probes are valuable tools for studying this important family of enzymes, despite the inherent difficulty of developing peptides targeted towards an individual PTP. Here, we have taken a rational approach to designing a SHP-2 targeted, fluorogenic peptide substrate based on information about the potential biological substrates of SHP-2. The fluorogenic, phosphotyrosine mimetic phosphocoumaryl aminopropionic acid (pCAP) provides a facile readout for monitoring PTP activity. By optimizing the amino acids surrounding the pCAP residue, we obtained a substrate with the sequence Ac-DDPI-pCAP-DVLD-NH2 and optimized kinetic parameters ( k cat  = 0.059 ± 0.008 s −1, Km  = 220 ± 50 µM, k cat /Km of 270 M −1 s −1 ). In comparison, the phosphorylated coumarin moiety alone is an exceedingly poor substrate for SHP-2, with a k cat value of 0.0038 ± 0.0003 s −1, a Km value of 1100 ± 100 µM and a k cat /Km of 3 M −1 s −1 . Furthermore, this optimized peptide has selectivity for SHP-2 over HePTP, MEG1 and PTPµ. The data presented here demonstrate that PTP-targeted peptide substrates can be obtained by optimizing the sequence of a pCAP containing peptide.